Enhancing Environmental Sustainability and Human Resource Development through Hybrid Coconut Planting in Assilulu Village, Maluku Tengah - Fransina Latumahina; Ince Aprilya Farah Azhari; Samsudin Keliulu (Indonesian Journal of Cultural and Community Development, 2023)
This scientific article presents the outcomes of a real work lecture, known as KKN, conducted by students from Pattimura University in Assilulu Village, Maluku Tengah. The objective of the study was to contribute to environmental preservation and human resource development by focusing on the planting of hybrid coconut seeds. The study employed a method involving the purchase of 20 coconut seedlings from local communities, which were then planted in vacant land owned by Assilulu Village, specifically in front of SD Negeri 170 Assilulu. The implementation of this initiative occurred on May 11, 2023, as part of the KKN program. The results of the study indicate that the community of Assilulu, with its abundant natural resources, can benefit from the maximization of these resources. The planting of hybrid coconut seedlings not only provides valuable insights into their cultivation but also contributes to the enhancement of human resources in Assilulu Village, thus achieving a balance between natural resources and human capital. This research highlights the importance of sustainable environmental practices and the cultivation of high-quality human resources in rural communities. It has implications for community-based initiatives aiming to promote environmental sustainability and human resource development in similar contexts. Highlight: Integration of knowledge: The KKN program allows students to integrate their academic knowledge with practical applications in the community, fostering a holistic understanding of their field of study. Environmental preservation: The focus on planting hybrid coconut seeds in Assilulu Village highlights the importance of utilizing natural resources sustainably and promoting greener practices for environmental preservation. Human resource development: The KKN initiative contributes to the development of high-quality human resources in Assilulu Village, aligning with the goal of creating a balance between natural resources and human capital. Keyword:Real Work Lectures, KKN, Higher Education, Community Integration, Hybrid Coconut Planting